Relationship between Organizational Behavior and Financial Management of Bank Tabungan Negara, Makassar City - Kurniawan, Agung Widhi (Abadi Institute, 2024)
Organizational behavior is the study of the behavior and habits of individuals within an organization. Understanding the behavior of this organization has a profound impact on the organization to achieve its goals. Most organizational activities are closely related to individuals. Therefore, individual behavior and habits before entering the organization need to be taken into account. With organizational behavior, an organization will run effectively and efficiently. This study aims to find out the relationship between organizational behavior and financial management of Bank BTN Makassar City. This study used a qualitative method by conducting an interview with one of the employees of Bank BTN Makassar City. Based on the interview results, there is a relationship between organizational behavior and financial management of BTN Bank. The relationship of BTN bank's organizational behavior with its financial management is that organizational behavior has a very significant effect on BTN bank's financial management. This is because organizational influence can lower the NPL.